2017
DOI: 10.1001/jamasurg.2017.0131
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computerized Clinical Decision Support Systems to Prevent Venous Thromboembolism in Surgical Patients

Abstract: Use of CCDSSs increases the proportion of surgical patients who were prescribed adequate prophylaxis for VTE and correlates with a reduction in VTE events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 47 publications
0
48
0
Order By: Relevance
“…These clinical decision support tools have been shown to significantly increase the appropriate ordering of VTE prophylaxis and to significantly decrease the rate of VTE. 15 This review provides evidence-based recommendations on the prevention of VTE in OHNS, weighing the risks and benefits of alternative and overlapping prevention strategies with a focus on the unique risks in the OHNS population. Owing to the paucity of specialty-specific evidence, these should not be considered clinical practice guidelines, nor are they meant to supplant personalized assessment in the context of the doctor-patient relationship.…”
mentioning
confidence: 99%
“…These clinical decision support tools have been shown to significantly increase the appropriate ordering of VTE prophylaxis and to significantly decrease the rate of VTE. 15 This review provides evidence-based recommendations on the prevention of VTE in OHNS, weighing the risks and benefits of alternative and overlapping prevention strategies with a focus on the unique risks in the OHNS population. Owing to the paucity of specialty-specific evidence, these should not be considered clinical practice guidelines, nor are they meant to supplant personalized assessment in the context of the doctor-patient relationship.…”
mentioning
confidence: 99%
“…In our previous review, multifaceted interventions were found to be the most effective system-wide intervention in observational studies 35. In the most recent systematic review and meta-analysis, the use of computer-based clinical decision support system in observational studies was associated with an increased rate of ordering appropriate thromboprophylaxis and a reduced rate of VTE in hospitalised surgical patients 57. The additional findings from our updated review compared with other reviews are most likely due to the inclusion of the largest number of RCTs involving a large number of hospitalised medical and surgical patients at risk of VTE.…”
Section: Discussionmentioning
confidence: 98%
“…Routine screening for all possible risk factors may be difficult and may not be cost-effective. Previous studies have suggested that the use of computerized clinical decision support systems may contribute to a more systematic screening of patients for risk factors and select appropriate patients for chemoprophylaxis to prevent VTE in surgical patients [34],…”
Section: Discussionmentioning
confidence: 99%